Teoria sobre atenção às necessidades em saúde: um olhar sensível para além da doença - Amanda Rodrigues Garcia Palhoni (2018)
Understanding the health needs of the users by professionals is essential to reach the integrality of care. There are political proposals and professional discourse that guide the integrality and practices based on the subjects. However, reality shows that there are offers of services following the menu of actions established in care protocols, aimed at individual care and illness, without considering the people directly involved in care and what goes on in their daily lives. The present research maintains that the health needs of the users of the Family Health Strategy are related to the daily life of the people and the space where they live, going beyond organic issues of the body and that the aspects according to which the values of care are built can only be understood in their relation to their contexts. In view of this, it is questioned: How are health needs established in the daily life of users served in the Family Health Strategy? What are the reasons why they seek health care? What are the health needs of these people who seek health services? What are health need for them? This study aims to understand and build the theorization about health needs of users in the daily life of the Family Health Strategy. It is a qualitative research, with theoretical reference in Symbolic and Methodological Interactionism in the Grounded Theory. Twenty-six users, women and men with and without children, were interviewed from a Basic Health Unit in the municipality of Nova Lima, Minas Gerais, from February 2016 to July 2018. The number of participants was given through sampling and theoretical saturation. The interviews were conducted at the Basic Health Unit and also at home, being guided by an open script. Data analysis followed the proposed stages of the Data Based Theory: open coding, axial coding and selective coding, and from this coding process, four concepts emerged: Health Concepts, Care Demands, Health Care Expectations and "Health could improve even more. The central category that emerged from this process and which brought together such concepts was the Attention to Needs in Health: a sensitive look beyond the disease. The health needs are based on the conceptions of health of the people, linked to the absence of what brings limitations to life, well being, quality of life, self-care and the establishment of social and affective relationships that; allied to the demands of care, which involve organic issues of the body and the search for care; indicate the assistance that goes beyond the treatment of diseases and provides health care based on relationships of trust, reception, receipt of information and responses. There is the recognition of the users of the service to their health needs, although they understand that there can be improvement in the services. It was evidenced subsidies that can contribute to reorientation of the assistance organization in the services and practices of the health professionals to meet the health needs.